Difficulties in the diagnosis and management of radial scar lesions detected by mammography - Nowikiewicz, Tomasz; Walentowicz, Małgorzata; Laskowski, Ryszard; Grabiec, Marek (Menopause Review/Przegląd Menopauzalny, 2009)
Background: Radial scar is a lesion in the breast with characteristic radiological features. The prevalence of radial scar (RS) is 0.04% in asymptomatic women participating in population screening for breast cancer. It is important to differentiate RS from concomitant malignancies or from small stellate carcinomas which give similar radiomorphology. The aim of the study was to evaluate the diagnosis and treatment of RS detected by mammography (MMG). Material and methods: 151 cases of RS that were set up by mammography were retrospectively analyzed (0.06% of all MMG scans performed in Oncological Center in Bydgoszcz in 2000-2008). Results: 94 women were included to the study group. First group of patients – sixty women (63.8%) underwent either surgical excision or vacuum assisted breast biopsy. Histology showed malignant lesions in 15 cases (16%). The second group of women – thirty four patients were followed regularly (no progressive changes were noticed in the consecutive MMG). Conclusions: In spite defined diagnostic criteria there are a lot of morphological patterns of radial scar. Due to high risk of beast cancer in women diagnosed with radial scar lesions detailed diagnostic procedures are necessary. In order to posses the final diagnosis histological examination is essential, if possible with the use of minimal invasive surgical techniques (through vacuum assisted breast biopsy).